Physical chemistry - Ball, David W., 1962- (Thomson-Brooks/Cole, 2020)
Gases and the Zeroth Law of Thermodynamics -- The First Law of Thermodynamics -- The Second and Third Laws of Thermodynamics -- Free Energy and Chemical Potential -- Introduction to Chemical Equilibrium -- Equilibria in Single-Component Systems -- Equilibria in Multiple-Component Systems -- Electrochemistry and Ionic Solutions -- Pre-Quantum Mechanics -- Introduction to Quantum Mechanics -- Quantum Mechanics: Model Systems and the Hydrogen Atom -- Atoms and Molecules -- Introduction to Symmetry in Quantum Mechanics -- Rotational and Vibrational Spectroscopy -- Introduction to Electronic Spectroscopy and Structure -- Introduction to Magnetic Spectroscopy -- Statistical Thermodynamics: Introduction -- More Statistical Thermodynamics -- The Kinetic Theory of Gases -- Kinetics -- The Solid State: Crystals